N fertilizer source and placement impacts nitrous oxide losses, grain yield and N use efficiency in no-till corn - Mendes Bastos, Leonardo (Kansas State University, 2014)
Agricultural lands receiving N inputs are considered the primary source of N2O, a potent greenhouse gas. N fertilizer management has shown variable effects on both N2O losses and corn grain yield. The objectives of this study were to assess the impact of N source and placement on N2O emissions, fertilizer-induced emission factor (FIEF), corn grain yield, yield-scaled N2O emissions (YSNE) and N fertilizer recovery efficiency (NFRE). The experiment was conducted from 2013 through 2014 at the Agronomy North Farm located at Kansas State University, Manhattan, KS. The soil was a moderately well-drained Kennebec silt loam. The treatments were broadcast urea (BC-Urea), broadcast urea ammonium nitrate (UAN) (BC-UAN), broadcast coated urea (BC-CU), surface-band UAN (SB-UAN), subsurface-band UAN (SSB-UAN), subsurface-band UAN + nitrification inhibitor (SSB-UAN+I) and a 0 N control. In 2013, SSB- UAN emitted significantly more N2O (2.4 kg N2O-N ha-1), whereas control (0.3 kg ha-1) and BC- UAN (0.6 kg ha-1) emitted the least. In 2014, most treatments emitted between 3.3 and 2.5 kg N2O-N ha-1. Only SSB-UAN+I (1.03 kg ha-1) and control (0.26 kg ha-1) were significantly lower. The use of a nitrification inhibitor decreased N2O emissions by 62% and 55% in 2013 and 2014, respectively. BC treatments had cumulative emissions significantly higher in 2014 compared to 2013. Only SSB-UAN+I had a significantly lower FIEF (0.4%), and 2013 FIEF (0.68%) was significantly lower than that of 2014 (1.38%). In 2013, banded treatments had significantly higher grain yields (from 9.1 to 10.5 Mg ha-1), whereas in 2014 fewer differences among N treatments were observed, ranging from 7.2 to 8.6 Mg ha-1. Banded treatments had significantly lower grain yields in 2014 compared to 2013. Only BC-UAN and SSB-UAN+I had significantly lower YSNE, and 2013 had lower YSNE than 2014. In 2013, SSB-UAN had the greatest NFRE, whereas BC treatments had the lowest. In 2014, N treatments did not differ in NFRE. SSB-UAN and SSB-UAN+I had significantly lower NFRE values in 2014 compared to 2013. Fertilizer source and placement have the potential to mitigate N2O emissions and promote high yields and NFRE in corn, however, the response is dependent on the rainfall pattern after fertilizer application. The option of banding UAN without any additive promoted higher N2O losses on a year when precipitation was well distributed, but also enhanced grain yield and NFRE. On the other hand, under the same precipitation conditions, broadcasting N fertilizer promoted lower N2O losses, grain yield and NFRE, but those were all improved in a wet year. Therefore, the subsurface band placement would be the best option under a normal year, whereas broadcasting fertilizer would be the best option under a wetter year. Further, the use of NI with subsurface band UAN provides the most sustainable option, since the NI decreased N2O losses compared to UAN alone in both years. Further research should evaluate N source and placement combinations under different environments in order to better understand how they impact crop performance and the negative environmental aspects of N fertilization. It is important to test those treatments under different precipitation scenarios and look for trends that indicate the best N management option at the local level.
Keywords: Nitrogen fertilizer; Nitrous oxide; no-till; corn; denitrification; Nitrogen use efficiency; Soil Sciences (0481)